Externalities of Sales Information Along the Supply Chain - Hao, Yamin; Wang, Xiaojia (Journal of Applied Business and Economics, 2024)
Prior studies have shown that earnings information of customer firms is value relevant to the investors of their suppliers, but it remains unclear whether sales information has similar effects. In this study, we investigate the value relevance of customer firms’ sales information to suppliers’ investors using a large sample of monthly sales disclosures from U.S. retailers. We find that within the narrow window of retailers’ monthly sales disclosures, suppliers’ abnormal stock returns are positively related to retailers’ sales growth in both same-store sales and store numbers. This finding suggests that sales information has spillover effects, or externalities, along the supply chain. We further conduct cross-sectional tests and find that the externalities of sales information vary with a supplier’s dependence on the retailer. We also develop a prediction model to separate the expected and unexpected components of retailers’ sales information and find that the unexpected component of sales growth is the primary source of externalities. Overall, this study provides new insights into the value relevance of sales disclosures.